A dimensão fraterna do direito penal e sua aplicabilidade nos delitos do colarinho branco no Brasil - Vilhena, Josimary Rocha de (2021)
This research was carried out with the purpose of presenting the possibility of applying fraternity in the penal area, more specifically to “white collar crimes”, through the respect and strengthening of the constitutional precepts in force in the Federal Constitution of 1988. We started from the perspective that strengthening the "due legal process" and the "principle of the humanity of penalties", with the help of restorative practices, can be a less harmful solution for society from the point of view of the application of criminal justice, through effective dialogue between human rights and the repressive norms currently in force at the national level. As shown in the body of the study, the world has been undergoing constant religious, social, political and economic changes, mainly due to the evolution of men. It is inevitable that, changing the perception of reality, the notions of Law and justice also undergo changes, as well as the way of administering justice. This work has been divided into five chapters, plus an introduction and conclusion. The cuts took place from the conceptual search for human rights, fraternity, white-collar crimes and, later, it travels through the concept and applicability of restorative justice, as an auxiliary alternative in the search for democracy, strengthening human rights and respect for the dignity of human person